A Brief Review on Structural Health Monitoring Sensor Technology in Civil and Aviation Technology Applications - Ariffin, Ahmad Hamdan; Mahzan, Shahruddin; Mohamad, Zaleha (Journal of Advanced Mechanical Engineering Applications, 2020)
Structural Health Monitoring (SHM) system is a method to evaluate and monitor the integrity of a structure. It has been widely applied in various engineering sectors such in aviation, civil, and energy due to its ability to response with structure changes at online basis or real-time monitoring. With continuous rapid development of sensor technology, SHM managed to be developed and employed in various kind of structures or component. It is believing that in the future years, the SHM will become an important tool in multi-industry for structure monitoring. Therefore, this paper will give a review on recent technology of SHM in civil and aviation technology application as well as the challenges in cost analysis and certification to implement the SHM.